(untitled) (Bangladesh Journal of Botany, 2018)
Out of 20, 40, 60 and 80 per cent moisture depletion 20% showed significantly higher grain yields, biological yield, chlorophyll a, b than the others. However, the highest contribution of stem and leaf dry matter remobilization in grain yield were obtained in 80% moisture depletion and 300 kg N/ha and the lowest one was found in the 20% moisture depletion and 150 kg N/ha. Nitrogen application increased all traits, however there were no significant difference between 250 and 300 kg N/ha.